1996
DOI: 10.1021/ic951044p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on Models for the Oxo-Transfer Reaction of Dioxomolybdenum Enzymes

Abstract: Patterned after synthetic model systems for dioxomolybdenum enzymes, our theoretical model system produces an energy profile and structures for the various species and oxidation states in the catalytic cycle. A key step in this cycle is the oxo-transfer reaction. Here, our substrate, PMe(3), approaches [Mo(VI)O(2)](2+) at an O-Mo-O-P dihedral angle of 90 degrees, i.e. perpendicular to the MoO(2) plane, crosses over a barrier of 14 kcal/mol, and rotates to an O-Mo-O-P dihedral angle of 0 degrees to form an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 19 publications
12
81
0
3
Order By: Relevance
“…In the oxo(phosphoryl) complex 3a the Mo-O2 bond is now a single bond (2.223 Å ), the P-O2 bond has formed (1.550 Å ), the O2-P-C1 angle has relaxed to 114.2°, the P-O2-Mo-O1 torsion angle is reduced to -53.6°and the Mo-O1 bond is shortened (formal triple bond) according to the spectator oxygen effect (Table S3) [3]. The results described for our system are fully compatible with previous computational studies of model systems [10][11][12][13][14][15][16][17][18].…”
Section: Modelling Of the Oat Half Cyclesupporting
confidence: 89%
“…In the oxo(phosphoryl) complex 3a the Mo-O2 bond is now a single bond (2.223 Å ), the P-O2 bond has formed (1.550 Å ), the O2-P-C1 angle has relaxed to 114.2°, the P-O2-Mo-O1 torsion angle is reduced to -53.6°and the Mo-O1 bond is shortened (formal triple bond) according to the spectator oxygen effect (Table S3) [3]. The results described for our system are fully compatible with previous computational studies of model systems [10][11][12][13][14][15][16][17][18].…”
Section: Modelling Of the Oat Half Cyclesupporting
confidence: 89%
“…For example, it has been shown that sulfite oxidation by sulfite oxidase enzymes, which can be viewed as a reverse reaction of nitrate reduction, proceeds through attack of the lone pair of electrons of the sulfur atom on one of the oxo ligands at the molybdenum. [16] Other computational studies of phosphine oxidation [17,18] have led to similar results. Two DFT investigations concerning DMSO reductase [24,25] and trimethylamine N-oxide reductase [25] have been published, in which model systems of the general form Mo IV OR(S 2 C 2 R' 2 ) 2 were used.…”
Section: Introductionsupporting
confidence: 56%
“…Three of these residues (Asp271, Arg89, and His91) are completely conserved throughout the entire SO family, possibly indicating a conserved mechanism for the oxo-transfer reaction catalyzed by NR and SO. The position of the reaction intermediate ( Figure 6D) was chosen by a planarity restrain for the nitrogen, nitrateoxygen, Mo, and the apical oxygen bonds according to the stereochemistry and reaction of model compounds (Pietsch and Hall, 1996), and reasonable distances to adjacent atoms were also considered. The resulting coordination of the bound nitrate involves Asp271 and Asn272.…”
Section: The Reaction Mechanism Of Eukaryotic Nitrate Reductionmentioning
confidence: 99%